(untitled) (Faridpur Medical College Journal, 2025)
Optic neuritis in children is rare and different from adult, often resulting in better visual outcomes despite initial severe vision loss. This observational study aimed to assess short term visual outcome of optic neuritis in children at National Institute of Neurosciences and Hospital in Bangladesh. A total of 24 children aged 5- 15 years with acute or subacute loss of vision were evaluated from January 2020 to June 2021. Comprehensive evaluation included history, examination, Cerebrospinal fluid (CSF) study, neuroimaging and anti- NMO Antibody testing. All children received intravenous methylprednisolone followed by oral steroid. Follow up of patients was done at discharge, 1 and 6 months. Mean age was 9.57±2.70 years with female (66.67%) predominance. Bilateral ocular involvement in 79.17% and ocular pain 75% of cases were main presenting features and isolated optic neuritis (79%) was the most common cause. Orbital MRI findings showed optic nerve hyperintensity were more in isolated optic neuritis (33.33%), where ADEM (8.3%) had abnormal brain MRI and ON-NMO (12.5%) had abnormal MRI of spine. Following treatment visual acuity showed improvement in all the eyes at discharge and it was statistically significant. Full recovery (20/20) was seen in 46.50% and 69.8% of cases at 1 and 6 months follow up respectively. Overall, most children responded well to steroid therapy despite poor vision at presentation and significant visual recovery was observed in majority of the cases at 6 months follow-up. Faridpur Med. Coll. J. 2025;20(2):18-24